Reliable Graph Routing in Industrial Wireless Sensor Networks. (5th December 2013) - Zhao, Jing; Qin, Yajuan; Yang, Dong; Duan, Junqi
Research studies on smart cities have been conducted, which will enable a better management of the available resources. Industrial wireless sensor networks (IWSNs) are important part of smart city. IWSNs are used for process measurement and control applications in harsh and noisy industrial environments. As substitutes for traditional wired industrial networks, IWSNs are more flexible, scalable, and efficient. However, resource limitation of the sensor nodes and unreliability of low-power wireless links, in combination with stringent quality of the service (QoS) requirements of industrial applications, imposes many challenges in designing efficient routing for IWSNs. Existing standards propose a simple and reliable routing mechanism named graph routing. In this paper, we propose novel routing algorithms to discover reliable paths and construct reliable routing graphs. In our approaches, the centralized manager selects parent nodes for each node in the network to satisfy reliability requirements of the intended application. We try to maximize the number of reliable nodes and change the parent nodes selection strategy along with the link quality and the link correlation. Our design is evaluated using simulation where we show that our algorithm could achieve a balance between routing reliability and overhead.